2015
DOI: 10.1088/0031-9155/60/22/8741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gafchromic EBT-XD film, with comparison to EBT3 film, and application in high dose radiotherapy verification

Abstract: There is renewed interest in film dosimetry for the verification of dose delivery of complex treatments, particularly small fields, compared to treatment planning system calculations. A new radiochromic film, Gafchromic EBT-XD, is available for high-dose treatment verification and we present the first published evaluation of its use. We evaluate the new film for MV photon dosimetry, including calibration curves, performance with single- and triple-channel dosimetry, and comparison to existing EBT3 film. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 21 publications
5
81
1
Order By: Relevance
“…[1][2][3][4][5][6] Such films have been used for in vivo and small field dosimetry as well as in high-dose gradient regions and other challenging scenarios owing to their high spatial resolution, water equivalency, and ease of use. [7][8][9][10][11][12][13][14][15][16] Radiochromic film response to ionizing radiation is manifested as a change in color, due to increase in the concentration of light absorbing polymers, which is characterized by the optical density (OD) or absorbance (A). 17 The absorbance measured using an optical system can then be correlated with the radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Such films have been used for in vivo and small field dosimetry as well as in high-dose gradient regions and other challenging scenarios owing to their high spatial resolution, water equivalency, and ease of use. [7][8][9][10][11][12][13][14][15][16] Radiochromic film response to ionizing radiation is manifested as a change in color, due to increase in the concentration of light absorbing polymers, which is characterized by the optical density (OD) or absorbance (A). 17 The absorbance measured using an optical system can then be correlated with the radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…The active layer of the EBT‐XD model is sandwiched between two matte polyester substrate each with 125 μm thickness, identical to that of the EBT3 model. There are several studies on the characterization and validation of the EBT‐XD films for radiotherapy dosimetry applications . These studies showed an improved performance of the EBT‐XD film over the EBT3 model for applications requiring doses greater than 10 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…Before performing patient‐specific QA of radiotherapy treatment plans with the Gafchromic EBT‐XD films, it is important to investigate their dosimetric characteristics. It has been reported that the lateral response artifacts associated with EBT‐XD films are significantly smaller than those associated with EBT3 films 17 , 18 …”
Section: Introductionmentioning
confidence: 99%